Unusual presentation of ectopic thyroid causing respiratory distress - Kathuria, Sunil; Sunny, Chikku (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Internal obstruction of the upper airways can be due to infection, anaphylactic reaction, congenital anomaly, foreign body inhalation or mass. The endoluminal presence of thyroid tissue in the trachea is a rare cause of airway obstruction. Only 14 well documented cases of intratracheal ectopic thyroid tissue have been reported in English literature since 1966. These lesions are mostly benign and nearly all patient present with symptoms of respiratory obstruction. This case report is of a lady who presented with upper airway obstruction due to subglottic ectopic thyroid tissue. An ectopic thyroid gland can develop if its normal migration is halted along this tract during embryogenesis. Subglottic location of ectopic thyroid is extremely rare. However, ectopic thyroid tissue in the larynx should be considered as a possible diagnosis causing upper airway obstruction.